KURANG VITAMIN C DAN TINGGI STRESS BERKAITAN DENGAN KENAIKAN KADAR GULA DARAH PASIEN RAWAT JALAN DIABETES MELLITUS TIPE 2 DI PUSKESMAS BINONG - Sifa Salsabila; Dudung Angkasa; Mertien Sapang; Nadiyah Nadiyah (Media Gizi Mikro Indonesia, 2023)
ABSTRACTBackground. Prevalence of diabetes mellitus (DM) increase significantly (3.4% in 2018) ifcompare to previous national survey (1.3% in 2010, 2.1% in 2013). More than half (51%)outpatient in Puskesmas Binong suffered from Type 2 DM (T2DM). No studies had examine therelationship between intake of vitamin C and chromium, dietary compliance, and stress levels inT2DM patients who lived in rural areal. Objective. To examine the relationship between intake ofvitamin C and chromium, dietary compliance, and stress levels with blood sugar levels inoutpatients T2DM. Methods. This was a cross sectional study that involved 90 outpatient T2DMaged 45-60 years old. Data on blood sugar levels were obtained from medical records, intake ofvitamin C and chromium assessed by semi quantitative food frequency (SQ-FFQ). Dietarycompliance (DM Dietary Compliance) and stress levels (DASS, Depression Anxiety Stress Scale)are assessed by validated structured questionnaires. Pearson correlation test was performed toanswer research question. Results. Almost a third of respondents had controlled blood sugarlevel. Majority patient complied with diet yet had inadequate chromium intake. All patients wereinadequate of vitamin C intakes. Habitual intake of vitamin C (p = 0.030, r = -0.22) and stresslevel (p = 0.000, r = 0.31) significantly associated with blood sugar levels. There is no significantcorrelation between intake of chromium (p = 0.209, r = 0.13) and dietary compliance (p = 0.29, r =-0.11) on blood sugar levels. Conclusion. Vitamin C intake and stress levels may modify bloodsugar levels in T2DM patients. Adequate intake of vitamin C and good mental health should bepromoted among this patients.ABSTRAKLatar Belakang. Prevalensi diabetes mellitus (DM) meningkat signifikan (3,4% pada 2018) jikadibandingkan dengan survei nasional sebelumnya (1,3% pada 2010, 2,1% pada 2013). Dari 1254pasien rawat jalan di Puskesmas Binong, lebih dari separuhnya (51%) mengalami DM Tipe 2(T2DM). Belum ada studi yang menilai kaitan asupan vitamin C, asupan kromium, kepatuhandiet, dan tingkat stress pada pasien non-komplikasi di wilayah pedesaan. Tujuan. Menganalisishubungan antara asupan vitamin C dan kromium, kepatuhan diet, serta stress dengan kadar guladarah pasien rawat jalan T2DM. Metode Penelitian. Penelitian potong lintang ini melibatkan 90responden usia 45-60. Data kadar gula darah menggunakan pengecekan secara sewaktudengan metode perifer diperoleh dari hasil rekam medis. Asupan vitamin C dan kromium dinilai dengan kuesioner frekuensi makanan semi kuantitatif (SQFFQ). Kepatuhan diet dinilai dengan kuesioner kepatuhan diet DM sedangkan tingkat stressdianalisis dengan kuesioner DASS (kuesioner depresi, kecemasan, stress). Analisis datamenggunakan uji korelasi Pearson. Hasil Penelitian. Hampir sepertiga (27.8%) respondenmemiliki gula darah terkendali, sebagian besar patuh diet dan kurang kromium. Seluruhresponden kurang vitamin C. Asupan vitamin C (p = 0.030, r = -0.22) dan tingkat stress (p =0.000, r = 0.31) berhubungan secara bermakna dengan kadar gula darah. Tidak adahubungan antara asupan kromium (p = 0.209, r = 0.13) dan kepatuhan diet (p = 0.29, r = -0.11) terhadap kadar gula darah. Kesimpulan. Asupan vitamin C dan tingkat stress dapatmemodifikasi kadar gula darah pada pasien DM rawat jalan. Pasien sangat dianjurkan untukmencukupi asupan vitamin C harian dan menjaga kesehatan mental.